Diseño de un manual de control interno para las Cooperativas de Ahorro y Crédito con aplicación práctica a la Cooperativa de Ahorro y Crédito Marcabelí del Cantón Marcabelí Provincia de El Oro - GALLARDO VÉLEZ, YULEYSI MABEL (2016)
This work titled "DESIGN OF A MANUAL OF INTERNAL CONTROL FOR THE SAVINGS AND CREDIT COOPERATIVES WITH PRACTICAL APPLICATION TO THE MARCABELÍ CANTÓN PROVINCE OF EL ORO COOPERATIVE OF SAVINGS AND CREDIT" was developed in function of the objectives set in the diagnosis The current administrative and financial situation through the interview with the executives, by proposing an internal control system that guarantees the optimal use of the resources available to the Marcabelí Savings and Credit Cooperative and in determining the main administrative and financial activities carried out By the cooperative, in order to establish the appropriate guidelines for correct operation. In order to comply with the aforementioned objectives, an interview was conducted with the manager of the cooperative and surveys were carried out with the administrative staff of the cooperative, in order to gather information on the need to implement an internal control manual To which they said yes, an imperative reason for the design of this essential control tool that will allow the institution to develop its activities, processes and financial administrative procedures guided by a physical means as established by the Manual of Internal Control. Finally, the manual of internal control is elaborated and presented in detail, so that managers and other officials use it for the benefit of the cooperative.